ANALISIS HAMBATAN PEMUTUSAN PERHATIAN - Fathin Nazirah Aulia; Novita Friska; Amanda Kasih Lestari; Bintang Aprila Damanik (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Attention disengagement is one of the main learning barriers experienced by children with Autism Spectrum Disorder (ASD). Children with autism often have difficulty maintaining focus, following instructions, and completing learning tasks. This condition affects students’ engagement and academic achievement. This study aims to analyze attention disengagement barriers, contributing factors, and instructional strategies used by teachers to address these challenges. A qualitative descriptive approach was employed using observation, in-depth interviews with teachers and parents, and documentation. The results show that attention disengagement is influenced by internal factors such as emotional regulation, sleep patterns, diet, and excessive screen time, as well as external factors including learning environment, teaching methods, and instructional media. Teachers applied interest-based learning, sensory media, activity breaks, and emotional approaches to improve students’ attention. This study highlights the importance of adaptive learning strategies and collaboration between teachers and parents in supporting children with autism.